Optimization of Mannitol-Sucrose Mixture in Lozenges Containing Temu Ireng, Curcuma, Sand Ginger, and Ginger Using the SLD Method - Arinda Nur Cahyani; Eko Hidayahturrohman Khumaeni; Indira Pipit Miranti; Iva Rinia Dewi; Yosi Soraya (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Reduced appetite, diarrhea, cough, and joint pain are common health issues. Traditional medicinal plants such as Temu Ireng, Curcuma, Sand Ginger, and Ginger have been used to treat these conditions. This study aims to optimize the formulation of lozenges containing these plants using a combination of mannitol and sucrose as excipients through the SLD (Simple Lattice Design) method. Five formulations with varying ratios of mannitol and sucrose (FI = 75:25, FII = 25:75, FIII = 100:0, FIV = 0:100, FV = 50:50) were prepared using wet granulation. Granule physical properties were evaluated, and the optimum formulation was identified using statistical analysis including normality tests and one-sample t-tests. The results indicated that FI (mannitol 75%, sucrose 25%) provided the most desirable characteristics, with excellent granule flow, compressibility, and uniformity in lozenge quality. This research contributes to the development of herbal lozenges with optimized excipient combinations, enhancing the efficacy and quality of traditional medicine products.